Akselerasi Pengembangan Pariwisata Indonesia yang Berkelanjutan - Sayuti, Memet Achmad (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2018)
The growth of world tourism industry was indicated by increasing 4,7% in 2014 compared to 2013, reach over 1.138 billion tourist. Tourism fundamentally generate economic activity in destination all around the world. Sustainability still become main issue in tourism development, pushed to balance between mass tourism and alternative tourism. This happens also in Indonesia, when "ocean axis" offered by President of Indonesian Republic has open the unbalance west and east Indonesia in development, including tourism which targeting 20 million tourist in 2019. We have to improve accesibility and facility to support tourist movement all over Indonesia. To protect Bali, we have to set Bali not only as an entry point but as exit point, make the journey more meaningful. Closed by happy ending in Bali. Five models is offered to spread out tourist surrounding Indonesia. Those models are possible to develop because it's suitable with national policy to accelerate tourism growing in Indonesia in a sustainable way. Cross province activity can give more benefit by creating alternative tourism and the tourists will get more choice to visit. Utilization of four technical unit assistant under Ministry of Tourism will bring more benefit to accelerate the program.